An analysis of the impact of a transformative action reflection inset model on teachers' understanding and classroom behaviour - Reeves, Cheryl Ann (University of Cape Town, 2016)
Includes bibliography. === This dissertation tests the core assumptions of a particular model for INSET (teacher in-service education and training). The study uses as an illustrative case study an INSET programme for junior primary teachers which self-consciously aligns itself with the assumptions underpinning the transformative action reflection model. The assumption of this model is that it is the impact of Courses on teachers' understanding and classroom behaviour of the model both in terms of technical practice and in terms of teachers' ability to employ appropriate practices which will bring about improvement in the quality of teaching and learning in classrooms. The enquiry entailed operationalising measures through which the core assumptions of the model could be tested. In particular the research entailed measuring whether an INSET course based on this model impacts on 1. a) teachers' understanding of a model for teaching; b) teachers' practice of the model in the classroom; and 2. assessing whether the impact can be judged as improvement in teaching quality. Instruments to measure the impact of the course on teachers' understanding and practice of new pedagogies have been constructed on the basis of explicit criteria drawn from the objectives of two Courses from the particular INSET programme used for the study. Qualitative and quantitative data are used to measure the impact of the two Courses on teachers' understanding and practice of the model. Assessing whether the impact can be said to be improvement in the quality of teaching involved using two independent experts in the field of junior primary teacher training. The craft experts used specially constructed schedules to observe videos of the lessons of a mixed sample of teachers who had attended the INSET course and judge the appropriateness of teachers' practices within specific contexts. Data from the study reveals reasonable evidence to support the assumption that, in terms of its objectives, the claims of the INSET model appear to be valid. The appropriateness of the classroom behaviour of those teachers who according to the study have demonstrated evidence of adequate understanding and practice or mastery of the model was singled out by the craft experts. However, data from the study also reveals that overall only a small band of teachers demonstrate adequate understanding and practice of the model and that, in spite of a quality intervention based on the INSET model, the focus of the teaching of most teachers in the sample selected is on teaching content and vocabulary rather than on teaching concepts, skills and strategies.